(untitled) (Communications in Computational Physics, 2008)
Using the gyrocenter-gauge kinetic theory, an electromagnetic version of the high frequency gyrokinetic numerical algorithm for particle-in-cell simulation has been developed. The new algorithm, being an alternative to a direct Lorentz-force simulation, offers an efficient way to simulate the dynamics of plasma heating and current drive with radio frequency waves. Gyrokinetic formalism enables separation of gyrocenter and gyrophase motions of a particle in a strong magnetic field. From this point of view, a particle may be viewed as a combination of a slow gyrocenter and a quickly changing Kruskal ring. In this approach, the nonlinear dynamics of high frequency waves is described by the evolution of Kruskal rings based on first principles physics. The efficiency of the algorithm is due to the fact that the simulation particles are advanced along the slow gyrocenter orbits, while the Kruskal rings capture fast gyrophase physics. Moreover, the gyrokinetic formalism allows separation of the cold response from kinetic effects in the current, which allows one to use much smaller number of particles than what is required by a direct Lorentz-force simulation. Also, the new algorithm offers the possibility to have particle refinement together with mesh refinement, when necessary. To illustrate the new algorithm, a simulation of the electromagnetic low-hybrid wave propagating in inhomogeneous magnetic field is presented.